An Examination of Best Practices for Survey Research with Agricultural Producers. Issue 4 (3rd April 2021) - Avemegah, Edem; Gu, Wei; Abulbasher, Abdelrahim; Koci, Kristen; Ogunyiola, Ayorinde; Eduful, Joyce; Li, Shuang; Barington, Kylie; Wang, Tong; Kolady, Deepthi; Perkins, Lora; Leffler, A. Joshua; et al.
Abstract: To improve the economic and environmental sustainability of agriculture, information is needed on how to target research, teaching, and outreach programs. However, conducting survey research in general, and with agricultural producers specifically, is increasingly challenging given issues such as declining response rates and limited resources. While studies examining the best practices for promoting higher response rates exist, few focus explicitly on agricultural producers. In three separate surveys conducted with agricultural producers in South Dakota in 2018 and 2019, we included experiments testing how token pre-incentives, a research partnership, and response mode options impacted response rates. We also examined how sample source and email augmentations influence survey responses. The study findings indicate that providing pre-incentives and multiple simultaneous response options can increase response rates with agricultural producers. On the other hand, email augmentation to mail surveys, sample source, and identification of select institutional research partnerships appear to have minimal effects.